Personality disorders elements, history, examples, and research - Maass, Vera Sonja (Health and psychology sourcebooks, 2019)
This book details 10 personality disorders and their effects on those who suffer from it and on family, friends, colleagues and the community at large. Chapters focus on symptoms, diagnosis, incidence, history, development, causes, effects, and costs. Includes case histories; Up Close sections illustrating how disorders manifest and affect a person's interactions and relationships; research and theories about each disorder; treatment approaches; and references--Publisher's website.